Effect of the media on morphology of Cryphonectria parasitica (Murr.) Barr isolates and their Vegetative Compatibility Groups - Kovács, Gabriella; Radócz, László (Acta Agraria Debreceniensis, 2015)
The most dangerous pathogen for the European and American chestnuts is the blight fungus Cryphonectria parasitica (Murrill) Barr. Short after its introduction a big number of chestnut trees were destroyed on the infested area. The control could be really complicated, because of the numerous vegetative compatibility groups of the fungus. There is a type that carries a mycovirus viz. hypovirus in the cytoplasm. We are able to control effectively this pathogen by using mycovirus-carrying strains (called hypovirulent fungal strains also). In laboratory it is easy to multiply the virulent and the hypovirulent strains of the fungus but do not easy to differentiate colonies visually on simple PDA medium. During our research, we tested different types of media, based on potato and chestnut bark extract respectively. It was observed that on potato medium the virulent strains produce more orange pigments. So it is more easy to differentiate virulent or hypovirulent isolates of chestnut blight fungus based on colony colour and morphology.